Hybrid Bioprinting of Chondrogenically Induced Human Mesenchymal Stem Cell Spheroids - De Moor, Lise; Fernandez, Sélina; Vercruysse, Chris; Tytgat, Liesbeth; Asadian, Mahtab; De Geyter, Nathalie; Van Vlierberghe, Sandra; Dubruel, Peter; Declercq, Heidi (Frontiers in Bioengineering and Biotechnology, 2020)
To date, the treatment of articular cartilage lesions remains challenging. A promising strategy for the development of new regenerative therapies is hybrid bioprinting, combining the principles of developmental biology, biomaterial science and 3D bioprinting. In this approach, scaffold-free cartilage microtissues with small diameters (< 200 µm) are used as building blocks, encapsulated in a photo-crosslinkable hydrogel and subsequently bioprinted. Spheroids of human bone marrow-derived mesenchymal stem cells (hBM-MSC) are created using a high-throughput microwell system and chondrogenic differentiation is induced during 42 days by applying chondrogenic culture medium and low oxygen tension (5%). Stable and homogeneous spheroids were created with a mean diameter of 116 µm, which is compatible with bioprinting. Cartilage microtissues were developed starting from 14 days in culture, observed by a glycosaminoglycan- and collagen II-positive extracellular matrix. Spheroids at this maturation stage were able to assemble at random into a macrotissue, driven by developmental biology tissue fusion processes, and after 72 hours of culture, a compact macrotissue was formed. In the next step, spheroids were assembled in a directed manner with high spatial control using the bio-ink-based hybrid bioprinting approach. Therefore, 14-day spheroids were combined with a photo-crosslinkable methacrylamide-modified gelatin (gelMA) as viscous printing medium to ensure shape fidelity of the printed construct. The photo-initiators Irgacure 2959 and Li-TPO-L were evaluated by assessing their effect on bio-ink properties and the chondrogenic phenotype. The encapsulation in gelMA resulted in further chondrogenic maturation observed by an increased production of glycosaminoglycans and a reduction of collagen I. Moreover, the use of Li-TPO-L lead to constructs with lower stiffness which induced a decrease of collagen I and an increase in collagen II production. After 3D bioprinting, spheroids remained viable and cartilage phenotype was maintained. Our findings demonstrate that hBM-MSC spheroids are able to differentiate into cartilage microtissues and display a geometry compatible with 3D bioprinting. Furthermore, for hybrid bioprinting of these spheroids, gelMA is a promising material as it exhibits favorable properties in terms of printability and supports the viability and chondrogenic phenotype of hBM-MSC microtissues. Moreover, it was shown that a lower hydrogel stiffness enhances further chondrogenic maturation after bioprinting.